Prediction of Energy Consumption of Turkey on Sectoral Bases by Arima Model - Ozturk, Suat; Ozturk, Feride (Energy Economics Letters, 2019)
Prediction of sectoral or total energy consumption for any country is very important issue to plan both short and long-term energy strategies and policies. In this study, the historical energy consumption data of four sectors and their total from 1970 to 2015 is used in a class of autoregressive integrated moving average (ARIMA) models to predict both sectoral and total energy consumption of Turkey for the next 15 years. The results indicate that Turkey's sectoral and total energy consumption will be following an upward trend during the forecast period. Energy consumptions of industry, transport, residential-commercial and public service and agriculture sectors and their total will continue to increase at an annual average rate of 1.59 %, 4.66 %, 2.97 %, 2.46 % and 3.93 %, respectively, in the next 15 years.